2011
DOI: 10.1038/leu.2011.286
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1b trial of atacicept, a recombinant protein binding BLyS and APRIL, in patients with chronic lymphocytic leukemia

Abstract: aberrations, altered drug metabolism, and enhanced cellular repair processes. In contrast, the median OS for the 14 patients undergoing an ASCT was not reached, suggesting perhaps continued response to alkylator-based therapy.Among the 74 patients, 31 had high-risk disease based on the presence of one or more of the following abnormalities (Del 13 by metaphase cytogenetics, hypodiploidy, del 17p, t(4;14) or t(14;16)). The median OS from the time of progression was 9.5 months for the high-risk group compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…By acting as a molecular decoy, it neutralizes the effects of BAFF and APRIL, blocking the activation of TACI, BCMA, and the BAFF-receptor. A phase Ib study of Atacicept demonstrated that intravenous doses of up to 27 mg/kg were well tolerated in 21 patients with refractory or relapsed CLL with one PR (ORR 5%) in the highest dose cohort [171]. …”
Section: Targeting the Microenvironment In Cllmentioning
confidence: 99%
“…By acting as a molecular decoy, it neutralizes the effects of BAFF and APRIL, blocking the activation of TACI, BCMA, and the BAFF-receptor. A phase Ib study of Atacicept demonstrated that intravenous doses of up to 27 mg/kg were well tolerated in 21 patients with refractory or relapsed CLL with one PR (ORR 5%) in the highest dose cohort [171]. …”
Section: Targeting the Microenvironment In Cllmentioning
confidence: 99%
“…The subjects with AA genotype had much higher risk of B-CLL (OR = 2.45; CI 95% = 1.10; 5.49; P = 0.025). Previously, this variant was reported in the preliminary study to be associated with biological response to atacicept in B-CLL patients (23). Rs3803800 had been also shown to be associated with the risk of SLE and higher serum level of APRIL (24,25).…”
mentioning
confidence: 95%
“…Two antihuman APRIL antibodies (hAPRIL.01A and hAPRIL.03A), which can effectively block the binding of APRIL to BCMA and TACI and prevent in vitro and in vivo APRIL-induced B cell activation, are currently being tested in B cell-derived diseases [30]. In addition, the efficacy and safety of atacicept (TACIIg), a recombinant fusion protein that inhibits BAFF and APRIL, have also been evaluated in two phase I studies in patients with relapsed and refractory B cell malignancies [31,32]. In these studies, atacicept demonstrated promising biological activity and slight toxicity [31,32].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the efficacy and safety of atacicept (TACIIg), a recombinant fusion protein that inhibits BAFF and APRIL, have also been evaluated in two phase I studies in patients with relapsed and refractory B cell malignancies [31,32]. In these studies, atacicept demonstrated promising biological activity and slight toxicity [31,32]. Thus, it is conceivable to speculate that the addition of novel anti-BAFF/ APRIL signaling system agents with conventional treatments may have a favorable impact on FL patient outcome.…”
Section: Discussionmentioning
confidence: 99%